Robustno bilateralno teleoperiranje s programirljivim vezjem FPGA - Franc, Marko (visokošolska dela, 2013)
The dissertation presents a control algorithm for scaled bilateral control that is de-signed in the virtual modal space and derived by using the sliding mode approach. This con-trol algorithm ensures chattering free performance, robustness to the system disturbances and it allows easy implementation. Moreover, it allows scaled bilateral teleoperation that is neces-sary when themaster device and the slave device are not the identical robot mechanisms. The control algorithm requires information of the master/slave positions and the external forces that act on the system. For position and velocity estimation the use of analog Hall sensors, which are nowa-days already built into the motor housing, are proposed. Such sensors can provide sufficient position and velocity information. The algorithms for position and velocity estimation are presented. The robust control algorithm for bilateral teleoperation is implemented by the FPGA circuit. The FPGA circuits are known for its high computational power and parallel execution of the processes that allows achieving high control rates. This was already recognized as a necessity for high-end control systems. This allows setting high cutoff frequencies of the im-plemented filters. These filters are usually utilized tofilter input signals, for speed measure-ment and in some cases also for external force estimation. High cutoff frequency is required for high-performance bilateral teleoperation. Hence, the FPGA circuit has rather limited hardware resources; logic circuit design may present a challenging task. Such design has to be carefully designed, especially for complex controlsystems; otherwise, the provided hardware resources might be insufficient. This thesis presents the design methodology, which allows the optimization of the hardware resources and the execution time of implemented processes. Moreover, such a design methodology allows a short design time. Performance of the proposed bilateral teleoperator, that includes analog Hall sensors and FPGA circuit, is experimentally examined. For this purpose, a simple experimental system was utilized. The experiments involve different scenarios (free motion, touching soft obstacles and touching hard obstacles) and different values of control parameters. The proposed bilateral teleoperator allows high-performance scaled bilateral teleoperation with high-haptic fidelity.
Keywords: bilateralno vodenje; Disertacije; estimacija hitrosti; FPGA; Hallovi senzorji; haptika; meritve položaja; opazovalnik zunanje sile; PLL; Robotika; Teleoperiranje; vodenje v drsnem režimu